Investigation of relief and environmental aspects by GIS to support the territorial management of viticulture in the Serra do Sudeste wine-growing region, Brazil - Hoff, Rosemary; Alberti, Rodrigo; Viel, Jorge Antônio; Pauletto, Henrique; Nhoatto, Millena Portella (GOT: Revista de Geografia e Ordenamento do Território, 2023)
Research Purpose: To analyze aspects of relief and land use in relation to environmental preservation, in order to evaluate more favorable areas for viticulture, using data from medium resolution satellites and free GIS software. Methodology: The digital elevation model (DEM) of ALOS image with a resolution of 12.5 m was used to obtain hypsometry, slope and sun exposure. A Sentinel 2 image was used to obtain land use by MAXVER classification, highlighting native forest with field support. The data were processed in the QGIS program and the integration of the data was done by crossing relief, land use and environmental aspects. The permanent preservation areas (PPA) were obtained by geoprocessing in GIS. Findings: Permanent preservation areas associated with the margin of rivers, lakes and slopes above 45% were generated. The areas of vineyards, some planted since the 1970s in the region, coincided in part with the areas recommended in this study, as well as a soil zoning done previously. Originality/Value: This study contributes to the territorial and environmental management of the viticultural area of Encruzilhada do Sul, Brazil, and can be used for other activities. Viticulture can also be expanded to areas indicated as favorable, as well as encouraging to be extended to other areas of the Serra do Sudeste wine region.